Bureaucratic Reform, Work Ethics, And Public Services: Keys To Success Integrity Zone At MAN Insan Cendekia Paser - Rahman, Yudi; Fauziannor, Fauziannor; Hamdi, Hamdi (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The development of the Integrity Zone (ZI) is the main strategy in bureaucratic reform to create a work environment that is free from corruption and improve the quality of public services. Madrasah Aliyah Negeri Insan Cendekia (MAN IC) Paser has implemented an Integrity Zone development program since 2020 as an effort to realize a Corruption-Free Zone (WBK) and a Clean Serving Bureaucratic Area (WBBM). However, in its implementation, MAN IC Paser faces various challenges, such as organizational complexity, limited resources, and lack of commitment and publicity regarding this program. This study aims to analyze the influence of bureaucratic reform, work ethics, and public services on the implementation of the Integrity Zone. The research method used is a quantitative approach with explanatory research. Sampling was carried out by census of 90 employees of MAN IC Paser, with an analysis technique using multiple linear regression through the F test and the t test. The results of this study show that Bureaucratic Reform, Work Ethics, and Public Service simultaneously and partially have a significant effect on improving the Integrity Zone in MAN Insan Cendekia Paser Regency, East Kalimantan. Of the three variables, Public Services have a dominant influence in forming an Integrity Zone at the Ministry of Religion of Paser Regency. The findings of this study emphasize that Public Service is the main factor in strengthening the Integrity Zone at MAN Insan Cendekia Paser and the Ministry of Religion of Paser Regency. To achieve this, more modern services, simpler procedures, and an effective complaint system are needed. Bureaucratic reforms are also important, such as improving personnel management, simplifying organizational structures, and performance-based supervision. In addition, work ethics need to be strengthened by discipline, transparency, and providing incentives for employees with integrity. These measures will create a more transparent, accountable, and service-oriented government.